1998
DOI: 10.1111/1467-8608.00102
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Towards Some Aspects Of Business Ethics Among Students From Countries In Transition: An Empirical Research

Abstract: In this paper certain parameters of ethical values and attitudes of students in economics from different countries are analysed (attitudes toward work and organisation; goals of work; readiness to work for common benefit, etc.). The basic question was whether, and to what extent, such attitudes differ in countries in transition (former communist countries of Central and Eastern Europe) compared with western countries with a developed market economy and Latin-American countries. On the basis of empirical resear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Need for cognition (IV) Faith in intuition (IV) Religiosity (IV) Conway and Peetz (2012) Theories of moral licensing and the moral self Grubisic and Goic (1998)…”
Section: Utilitarian Inclinationmentioning
confidence: 99%
“…Need for cognition (IV) Faith in intuition (IV) Religiosity (IV) Conway and Peetz (2012) Theories of moral licensing and the moral self Grubisic and Goic (1998)…”
Section: Utilitarian Inclinationmentioning
confidence: 99%
“…, Jaffe & Tsimerman , Korka , Kooskora , , Ryan , Soboleva , Alas & Tafel , Pučetaite & Lämsä , Stoian & Zaharia , Pučetaite et al . ); other studies adopt a comparative approach between several post‐communist economies with the aim of identifying common CSR issues as well as cross‐country differences in adoption of CSR (Rees & Miazhevch ); finally, some papers adopt a comparative approach between CSR in transition countries and CSR in the West (Grubisić & Goić , Koleva et al . ).…”
Section: Csr In Transition Economies: a Review Of Extant Literaturementioning
confidence: 99%
“…In terms of 'contextualising' the debate on CSR in transition economies, the research conducted so far supports Campbell's (2007) view that institutions shape the nature of CSR in a country, hence studies vary in focus. Many papers are country specific (Apressyan 1997, Bohatá 1997, Al-Khatib et al 2004, Jaffe & Tsimerman 2005, Korka 2005, Kooskora 2006, 2008a, b, Ryan 2006, Soboleva 2006, Alas & Tafel 2008, Pučetaite & Lämsä 2008, Stoian & Zaharia 2009, Pučetaite et al 2010; other studies adopt a comparative approach between several post-communist economies with the aim of identifying common CSR issues as well as crosscountry differences in adoption of CSR (Rees & Miazhevch 2008); finally, some papers adopt a comparative approach between CSR in transition countries and CSR in the West (Grubisić & Goić 1998, Koleva et al 2010. This latter strand of literature argues that CSR in transition economies is different from that in the 'West' (Steurer & Konrad 2009).…”
Section: Contextualising Csr In Transition Economiesmentioning
confidence: 99%
“…There have been various studies designed to measure attitudes of the citizenry of these economies in transition. For instance, Grubišić and Goić (1998) found that ''…in former communist countries there exists a significant inclination towards individualist and egocentric attitudes in the sphere of business culture and business ethics.'' This finding may or may not translate into increased cynicism for the market as such or a view of profit-making as immoral.…”
Section: Historical Surveymentioning
confidence: 99%